Protein Changes in Different Tissues of Freshwater Bivalve Parreysia cylindrica after Exposed to Indoxacarb - A. G.*, Patil (Recent Research in Science and Technology, 2011)
Alteration in protein content was studied in freshwater bivalve Parreysia cylindrica exposed to acute (24 and 96 hours) and chronic (7 and 21 days) dose of indoxacarb in mantle, foot, gill, digestive gland and whole body tissue. There was significant decrease in over all protein content in mantle, foot, gills, digestive glands and whole body tissue of Parreysia cylindrica due to acute and chronic exposure to pesticide indoxacarb. The depletion was maximum in digestive glands than in mantle, gills, foot and whole body tissue. Pesticidal stress might have increased the proteolysis activities in the cells.